Simulation: An Effective Method of Teaching Cosmetic Botulinum Toxin Injection Technique. (3rd July 2018) - Mitkov, Mario V; Thomas, Colleen S; Cochuyt, Jordan J; Forte, Antonio J; Perdikis, Galen
Abstract: Background: Learning to inject botulinum toxin for cosmetic purposes is difficult for beginners, given the nature of the procedure and patient population. Simulation training is an effective modality for medical professionals to acquire skills in an environment that provides low stress and ample opportunity for questions and correction of mistakes. Objectives: Compare posttraining comfort, knowledge, and practical botulinum toxin injection scores among trainees who underwent simulation vs video training only. Methods: A total of 20 nurse practitioners, physician assistants, and resident physicians underwent cosmetic botulinum toxin injection training either through lecture and video, or lecture and hands-on simulation training. Comfort, knowledge, and practical test scores were recorded and compared between the groups. Results: There was no evidence of a statistically significant difference in comfort or knowledge scores between simulation and video groups. The median (range) practical score was significantly higher in the simulation group compared to the video group (59.0 [31-60] vs 44.5 [27-57]; P < 0.01). Conclusions: Despite feeling similarly comfortable and having similar written knowledge test scores, the trainees who underwent simulation training had significantly higher hands-on practical test scores compared to trainees who underwent video training only for cosmetic botulinum toxin injections.